Дослідження впливу ультрафіолетового випромінювання на посилення антимікробних властивостей препарату «Екоцид» - Книжка, Т.С. (Енергетика і автоматика, 2017)
RESEARCH ULTRAVIOLET RADIATION AT ENCHANCING THE ANTIMICROBIAL PROPERTIES OF THE DRUG «EKOCYD»T. Knizhka, Ph.D.The effect of ultraviolet radiation on the antimicrobial properties of aqueous solutions of the drug «Еkocyd». Defined effective disinfectant exposure to ultraviolet radiation.Keywords: ultraviolet radiation, disinfectant, photoactivation, irradiation of aqueous solutions.The research of liquid media exposure of ultraviolet radiation exposure proved the effectiveness of this method for the activation properties of irradiated materials [1-3]. Since ultraviolet radiation is a natural and given the low cost of this method of exposure to the substance, there is interest in conducting research on the impact of UV water disinfectant solutions and identify effective modes of its exposure.The purpose of research - the study of the influence of ultraviolet light emission range on the antimicrobial properties of aqueous solutions of disinfectant and determination of the effective exposure to ultraviolet radiation disinfectant.Materials and methods of research. As a source of UV lamp used ДРТ-400 with a wave maximum λ = 365 nm. The distance between the radiation source and the surface of the liquid was 0,25 m. Activated fluid paid in on agar medium immediately after seeding bacteria on it. The degree of bacterial growth was recorded 24 hours after treatment environment with bacteria activated liquid.For the cultivation of microorganisms used agar - universal dense environment on a natural basis, consisting of meat broth and agar (0,5…2 %). The material of bacteria Staf. aureus were collected from sick animals with pus, mucus from the throat, sputum, urine and blood.Results. In order to study the mechanism of UV radiation on the physical characteristics of the disinfectants solutions to electric chair and electrotechnologies NULES of Ukraine held measuring pH, redox-potential and salt content disinfectant solution immediately after exposure and during the period of aftereffect.Analysis of the results shows that ultraviolet radiation exposure from 2-10 min significantly change the pH and redox-potential of water solution of disinfectant. Prolong exposure slightly changes the parameters studied.In the Department of Microbiology NULES of Ukraine we conducted microbiological research on determining the impact on growth of Staphylococcus disinfectant properties «Ekocyde» and exposed to ultraviolet radiation with different exposures aqueous solution of disinfectant.In order to identify the economic effects using disinfectant after exposure concentrations taken 10 times less than recommended, such as «Ekocyde» - 0,1 %. Exposure disinfectant solution - 2, 5, 10 and 15 minutes.As a result of studies on the impact of radiation aureus solution of «Ekocyde» found that irradiation does not affect the antibacterial properties of the solution.ConclusionsUltraviolet radiation significantly alters the pH and redox-potential of aqueous solutions of disinfectants. Intensity pH change is characteristic of ultraviolet radiation exposure from 2-10 minutes.Established that exposure does not affect the antibacterial properties 0,1 % solution of «Ekocyde».